Colorectal cancers occurring after colonoscopy with polyp detection: sites of polyps and sites of cancers - Brenner, Hermann; Chang-Claude, Jenny; Jansen, Lina; Seiler, Christoph; Hoffmeister, Michael (International journal of cancer, 2013)
Colonoscopy with detection and removal of neoplasms strongly reduces risk of colorectal cancer (CRC). Nevertheless, CRCs occur after colonoscopic polypectomy. We assessed agreement beyond chance of location of polyps detected at colonoscopy and of subsequent CRCs to estimate the share of cancers that might be due to field effects or neoplasm recrudescence. In a population-based case-control study conducted in Germany (3,148 cases), detailed history and results of colonoscopies conducted within 10 years before cancer diagnosis were obtained by interview and from medical records. We determined the observed proportion of cancers for which a polyp had been detected at the same colorectal subsite at the preceding colonoscopy and compared it to the proportion expected by chance. A total of 155 cases with physician validated polyp detection at the preceding colonoscopy were identified. Among 148 cases with cancer restricted to a single subsite, 43 (29.1%) had a polyp detected in the same colorectal subsite at the preceding colonoscopy. Agreement of location of cancer occurrence and preceding polyp detection would have been expected by chance for 27 cases, and agreement beyond chance was estimated to account for 16 cases (10.8%, 95% confidence interval 2.7%-19.3%). Our study suggests that less than one of nine CRCs occurring within 10 years after colonoscopy with polyp detection may be due to field effects or polyp recrudescence.
Gesehen am 04.12.2020